Red Betel Leaf (Piper crocatum) Mouthwash for Effective Plaque Control and Halitosis Prevention: A Pre-Experimental Study - Suci Erawati; Susanto; Muhamad Wandy Arianto (Open Access Indonesian Journal of Medical Reviews, 2025)
Halitosis, or bad breath, is a prevalent oral health issue primarily caused by volatile sulfur compounds (VSCs) produced by the microbial breakdown of food particles in the oral cavity. The accumulation of dental plaque, a biofilm composed of bacteria and their byproducts, provides a conducive environment for VSC production. Red betel leaf (Piper crocatum) has been traditionally used for its medicinal properties, including its potential benefits for oral health. This study aimed to investigate the effectiveness of red betel leaf mouthwash in controlling plaque and preventing halitosis. A pre-experimental study design with a one-group pretest-posttest approach was employed. Participants were recruited from a high school student council, with a sample size of 20 students. The intervention involved the use of red betel leaf mouthwash over a period of one week. The plaque index was assessed using the Loe and Silness index before and after the intervention. Data were analyzed using the paired T-test to determine the significance of changes in the plaque index. The mean plaque index before using the red betel leaf mouthwash was 2.15 ± 0.676, which decreased significantly to 0.94 ± 0.562 after one week of intervention (p = 0.000; p < 0.05). This indicates a substantial reduction in plaque accumulation following the use of red betel leaf mouthwash. Red betel leaf mouthwash demonstrated significant efficacy in reducing plaque index, suggesting its potential as an effective natural alternative for plaque control and halitosis prevention. Further research with larger sample sizes and control groups is recommended to confirm these findings and explore the long-term effects of red betel leaf mouthwash on oral health.